Ekoliterasi Lingkungan Hidup dalam Alquran Perspektif M. Quraish Shihab - Agri, Imam Habib; Zein, Achyar (Kamaya: Jurnal Ilmu Agama, 2024)
Religion has an important role in guarding progress in the millennial era, so that it can be in line with the goal of creating humans as civilization-building creatures based on environmental awareness. Studying environmental issues from a religious perspective is also an idea that needs to be followed up. The existence of religion is able to influence its adherents to do good and care about the environment, and can be used as an alternative solution in solving the issue of environmental damage. This research aims to explore environmental ecoliteracy in the Koran and analyze Quraish Shihab’s interpretation of the Koranic verse about environmental ecoliteracy. This research is descriptive-analytic in nature where the author analyzes Quraish Shihab’s understanding of his interpretation of verses related to environmental ecoliteracy. This study found that the environment in the Koran can be applied into three parts. First, related to the earth which includes water, wind and land. Second, related to flora, including plants and fruit. Third, related to fauna which includes livestock. Furthermore, there are two dimensions of ecoliteracy in Quraish Shihab's interpretation. First, the essence of ecoliteracy itself, namely concern for the environment in the form of caring for the earth. Second, in order to keep the earth sustainable, a prohibition was created on destroying nature. Quraish Shihab is a person who is aware of the environment, which is strengthened by Quraish Shihab's statement which emphasizes that protecting nature is part of the Shari’a.